Increases in orbitofrontal cortex thickness following antidepressant treatment are associated with changes in resting state autonomic function in adolescents with major depression: preliminary findings from a pilot study - Koenig, Julian; Kaess, Michael (Psychiatry research. Neuroimaging, 2018)
In adults with major depressive disorder (MDD), effective treatment has been associated with increases in both heart rate variability (HRV) and cortical thickness. However, the impact of treatment on these indices has not yet been examined in adolescents.
Gesehen am 03.12.2019